The Effect of Arterial pH on Oxygenation Persists Even in Infants Treated with Inhaled Nitric Oxide - Barton, Aimee M.; Abubakar, M. Kabir; Berg, Jennifer; Keszler, Martin (Pulmonary Medicine, 2011)
Objective. To validate the empiric observation that pH has an important effect on oxygenation in infants receiving iNO. Study Design. Demographics, ventilator settings, arterial blood gases (ABG), and interventions for up to 96 hours of life were extracted from the charts of 51 infants receiving iNO. Need for ECMO and survival to discharge were noted. Mean blood pressure (MBP) and mean airway pressure (MAP) were recorded. The arterial/alveolar (a/A) ratio was used as the primary outcome. Analysis was by simple linear regression and multiple linear regression analyses and Fisher's exact test. pH responsiveness was arbitrarily defined as a correlation coefficient (CC) of >0.40 with P<0.05. Results. Mean gestational age was 38.8 weeks and mean birth weight was 3300 g. All patients had clinical diagnosis of PPHN. Clear responsiveness to pH was found in 31/51 infants. MAP and MBP did not correlate with a/A ratio. Three responders had a critical pH > 7.55. Of 11 patients requiring ECMO, only 3 exhibited responsiveness at any time in their course. Three responders required ECMO. Conclusion. This small study suggests that failure or inability to optimize pH may account for observed unresponsiveness to iNO. Maintaining a pH > 7.5 using hyperventilation is not recommended.